GEOLOGICAL EVIDENCES FOR THE TIBETAN PLATEAU UPLIFTED IN LATE OLIGOCENE - Wu Z.; Hu D.; Ye P.; Zhou C. (My University, 2007)
Most geologists believe that uplift of the Tibetan Plateau is geodynamically related to shortening and thickening of the crust, further more which cause the change in monsoon intensity and the ecological shift in Asia. However, uplift time of the Tibetan Plateau is still unsolved. Statistical analyses of dip angle of Cenozoic strata outcropped in central Tibetan Plateau indicate that major shortening and thickening of the crust occur in Paleogene, and lacustrine strata kept horizontal and gently dipping over vast areas since Early Miocene. Sporopollen assemblages contained in lacustrine strata in the region show that tropical-subtropical broad-leaved trees decrease from Middle Eocene to Late Oligocene and almost disappear since Early Miocene while dark needle-leaved trees increase in Early-Middle Oligocene and flourish or dominate in Early-Middle Miocene. These data, together with climate change and chronological dating, indicate that the central Tibetan Plateau uplifted to ∼4000 m in Late Oligocene.
Keywords: LACUSTRINE STRATA; SPOROPOLLEN ASSEMBLAGE; TIBETAN PLATEAU UPLIFT; VEGETATION CHANGE; Oligocene; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен